A study of best positive predictors for sustained virologic response to interferon alpha plus ribavirin therapy in naive chronic hepatitis C patients - Idrees, Muhammad (BioMed Central, 2009)
BACKGROUND: The aim of this study was to determine the rate of sustained virological response (SVR) and various factors associated with response rates in chronic hepatitis C infected patients treated with interferon alpha and ribavirin combination therapy. METHODS: A retrospective review of patients data collected at this Centre from 2001 to 2007 was performed. Out of 731 consecutive patients 400 patients that fulfilled the study criteria were evaluated and subsequently treated with a combination of interferon alpha 2b (3 MU subcutaneously three injections weekly) and ribavirin (800–1200 mg orally daily). Treatment were administered for either 24 weeks or 48 weeks and patients were followed for an additional 6 months thereafter. End of the treatment response (ETR), SVR and side effects were recorded. RESULTS: Out of 400 patients, 394 completed the entire treatment course and six patients discontinued treatment at month 2. Over 67% responded at the end of treatment and 16% suffered relapse. Among all treated patients, 47.6% males and 56.7% females had sustained viral response with a total combined sustained viral response rate of 50.5%. Rapid response was seen in 46.5% patients. In a multivariate logistic regression analysis, slow virological responders (adjusted OR 2.6 [95% CI 1.9–3.7]), HCV genotype 1&4 (adjusted OR 2.4 [95% CI 1.7–3.5]), pre-treatment viral load > 0.2 MIU/mL (adjusted OR 2.2 [95% CI 1.8–4.2]), Panjabi ethnic group (adjusted OR 1.6 [95% CI 1.0–3.2]) and Age > 40 years (adjusted OR 1.5 [95% CI 0.9–2.4]) were independent risk factors for non response. Side effects were usual and tolerable and only 1.5% discontinued the treatment. CONCLUSION: The best positive predictor for SVR in this country are: rapid virologic response, HCV genotype 2 & 3, age < 40 years, ethnic race Pashtoons and pre-treatment viral load < 0.2 million IU/mL.